PENGARUH SISTEM INFORMASI MANAJEMEN TERHADAP KINERJA ASN PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN KARO - Frans Banta Tarigan; Parapat Gultom (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
This study aims to find out and examine whether there is an effect of implementing management information systems on employee performance at the Karo Regency Personnel and Human Resource Development Agency. This study used descriptive quantitative methods, research data were collected using questionnaires in the form of checklists, observations and documentation. the data was analyzed using descriptive statistics with a simple linear regression formula, the data is explained in tabular form, frequency, narrative of the processed data with the help of SPSS 16. The results of the study show that the implementation of the management information system has been going well but there are still obstacles in its application such as inadequate facilities and infrastructure Lack of skills from employees who do not clearly understand how to use this management information system application, there must be an acc system from data processing which can hinder work, because they still have to wait for the acc. Judging from the results of the study, it shows that the implementation of management information systems on employee performance has been going well and has a partial effect, there is one indicator that has the greatest influence on work productivity, namely the delivery of information. This can be seen from the results of the partial linear regression test, namely data collection of 0.056 and from the results of the simultaneous linear regression test, it has an effect of 0.464 or 46.4% which affects work productivity, the rest is influenced by other variables that have not been examined by researchers.